2016
DOI: 10.2298/jsc150927022t
|View full text |Cite
|
Sign up to set email alerts
|

Interpretative optimization of the isocratic ion chromatographic separation of anions

Abstract: Interpretive retention modeling was utilized to optimize the isocratic ion chromatographic (IC) separation of the nine anions (formate, fluoride, chloride, nitrite, bromide, nitrate, phosphate, sulfate and oxalate). The carbonate-bicarbonate eluent was used and separation was done on a Dionex AS14 ion-exchange column. The influence of combined effects of two mobile phase factors, the total eluent concentration (2-6 mM) and the carbonate/bicaronate ratio from 1:9 to 9:1 (which correspond to pH range 9.35-11.27)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…17 The derivatization process is often troublesome, and it was shown that the application of IC for LMW organic acids analysis is more advantageous than GC-MS. 18 An optimized IC method can readily measure the major cations (sodium, ammonium, potassium, magnesium, calcium) and inorganic anions (chloride, nitrate, sulfate, oxalate, phosphate, bromide), even if they are present at a very low level in aqueous solution. [19][20][21] Here, an isocratic IC in the cation-exchange mode is applied for the analysis of five common cations, whereas twelve inorganic anions and LMW organic acids were simultaneously analyzed by an anion-exchange gradient IC.…”
Section: Introductionmentioning
confidence: 99%
“…17 The derivatization process is often troublesome, and it was shown that the application of IC for LMW organic acids analysis is more advantageous than GC-MS. 18 An optimized IC method can readily measure the major cations (sodium, ammonium, potassium, magnesium, calcium) and inorganic anions (chloride, nitrate, sulfate, oxalate, phosphate, bromide), even if they are present at a very low level in aqueous solution. [19][20][21] Here, an isocratic IC in the cation-exchange mode is applied for the analysis of five common cations, whereas twelve inorganic anions and LMW organic acids were simultaneously analyzed by an anion-exchange gradient IC.…”
Section: Introductionmentioning
confidence: 99%